A new amino-alcohol originated from carbon dioxide and its application as chain extender in the preparation of polyurethane. (July 2018) - Li, Xiaoyun; Ke, Jiexi; Wang, Junwei; Liang, Chen; Kang, Maoqing; Zhao, Yuhua; Li, Qifeng
Graphical abstract: Highlights: CO2 -sourced polyurethane urea chain extender was synthesized. The chain extender is an alcohol amine compound. Films from CO2 -sourced chain extender show good water and solvents resistance. Stronger hydrogen bond existed in CO2 -sourced polyurethane urea. PUU films from CO2 -sourced chain extender show other considerable properties. Abstract: In this work, CO2 was chemically fixed by reacting with 1, 4-butanediol diglycidyl ether in the presence of a basic polystyrene resin catalyst. Under the 100% conversion of 1, 4-butanediol diglycidyl ether, five-membered cyclocarbonate with a selectivity of 98.5% was obtained. The cyclocarbonate was then reacted with an excess of 1, 2-ethylenediamine and the product was characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance spectrometer. The results confirmed the successful synthesis of NH2 terminated product with a selectivity of 98.9%, accompanied by the formation of hydroxyls on β-C to the carbonyl groups, which can be regarded as a new amino-alcohol. Further, the obtained amino-alcohol was applied for the preparation of polyurethane urea as chain extender in a prepolymer way. Since the reactivity of isocyanate with NH2 is much faster than that with OH, the OH groups can be maintained in the system and hence strengthen the hydrogen bonding in polyurethane urea, which endows the materials with some unique properties. Comparing with the polyurethanes yielded from 1, 6-hexanediamine and 1, 6-hexanediol, polyurethane urea synthesized from the new amino-alcohol possessed better water/solvents resistance, considerable mechanical and thermal properties.